National Intellectual Capital Taxonomy - Michalczuk Grażyna; Fiedorczuk Julita (Economics and Business)
The concept of national intellectual capital (NIC) is in its early stage of development. NIC has a complicated and heterogeneous nature with NIC models displaying varying levels of aggregation and structure as well as inconsistent accuracy. As a result, the authors’ standpoints differ according to definition and NIC taxonomy. The aim of this article is to analyze NIC taxonomy and to organize and classify the scattered and often inadvertent intangible generators of the country’s wealth. The results of the research confirm a lack of a generally accepted definitional and taxonomic approach to NIC making a search for an acceptable solution necessary since without it the measurement and comparability of results or even the management and control of the intellectual capital of the country will not be possible. Besides contemplating the existing approaches of NIC division, the authors create their own NIC taxonomy and describe its components by presenting an original understanding of NIC components. This is extremely important because the subject of NIC has not yet been scientifically sufficiently exhausted.